SOSIALISASI UU “PKDRT” MELALUI FOCUS GROUP DISCUSSION UNTUK MENINGKATKAN PEMAHAMAN DAN MENGETAHUI PENDAPAT TENTANG KDRT PADA WANITA DI KODYA YOGYAKARTA - Rizqie Auliana (Jurnal Penelitian Humaniora, 2008)
Men and women in Constitution State of Republic of Indonesia 1945 are same. This position becomes imbalance after the issue of UU RI No. 1 Year 1974 on marriage, which is considered as the cause of domestic abuse. Domestic abuse increases in number with women as the victims. It results in trauma suffered by women which lead them to be powerless. Therefore, this abuse must be stopped. Law to eliminate domestic abuse is issued by Ministry of Women Empowerment through UU No. 23 Year 2004. Various kinds of socialization have been conducted to prevent the spread of this abuse in society. Due to the limitation of infrastructure, the socialization does not meet all areas yet. Therefore, this research socializes the Law by focus group discussion. This research aims to increase women’s understanding on domestic abuse and to know their opinion on it. The result of the research shows that the women’s understanding on domestic abuse increases from 85,8 5% to 91,65% after socialization. The samples also understand the existence of UU KDRT (Law on Domestic Abuse) and its aim. They also understand that domestic abuse is not only physical violence but also psyches, economical, and sexual abuse